Chronic low back pain in high level cyclists: comparison between two different treatments - Pogliacomi, F.; Pedrini, M. F.; Pellegrini, A.; Schiavi, P.; Ceccarelli, F.; Costantino, C. (Medicina dello Sport, 2016)
BACKGROUND: Cyclists are constantly subjected to repeated stress at the level of the lumbar spine. In these athletes a significant functional overload of the spine is consequent to the maintenance of prolonged fixed positions and of the mechanical stresses due to vibration on the bicycle, thus determining the loss of its physiological curve. The high incidence of low back pain in cycling leads us to consider prevention as the primary approach and management of these symptoms. The purpose of this study was to compare two treatments in cyclists suffering from chronic low back pain. METHODS: Twenty-two cyclists who cover more than 20,000 km/year were divided into two groups depending on the treatment performed. The first (group A) was subjected to Back School therapy, associated with changes of position on the saddle after its evaluation which was carried out with the seat cover "Geobiomized®". The second (Group B) underwent only to Back School. Each athlete was evaluated before treatment (T0) and after its completion (T1) using the following rating scales: Numeric Rating Scale, Oswestry Disability Index and Roland Morris Disability Questionnaire. RESULTS: The analysis of the results showed a significant improvement in both groups at T1 for all rating scales. The inter-group analysis showed better results in group A for the Roland Morris Disability Questionnaire that is characterized by a higher specificity for high-level athletes. CONCLUSIONS: Chronic low back pain may negatively influence sports performance. In cycling a correct position on the bicycle and the consequent improvement of the specific technical gesture are certainly useful in order to treat and prevent this debilitating symptomatology. This study shows that correction of the position on the saddle following specific analysis, associated with validated rehabilitative treatments might result in a reduction of lumbar pain and improvement of specific performance.